Impact of aerosols of sea salt origin in a coastal basin: Sydney, Australia. (15th June 2019) - Crawford, Jagoda; Cohen, David D.; Chambers, Scott D.; Williams, Alastair G.; Atanacio, Armand
Abstract: Sea salt is one of the major aerosols in the atmosphere in both the fine and coarse size ranges. Newly formed sea salt particles have a similar composition to seawater; including elements such as Na, Cl, Mg, S, Ca, Br and K. However, once in the atmosphere sea salt particles can undergo chemical reactions with other airborne pollutants, resulting in a loss of chlorine (whereas Na is conservative). The modified aerosol is commonly referred to as aged sea spray or aged sea salt. Fine aerosols from two sites in the Sydney Basin were analysed for source fingerprints with components that may have originated from the ocean (i.e. fresh and aged sea spray). At Lucas Heights, 18.4 km from the nearest coast, the average source fingerprint concentrations of fresh and aged sea spray were 0.47 ± 0.02 and 1.08 ± 0.03 μg/m 3, respectively. At Richmond, 58 km from the coast, the average fingerprint concentrations of fresh and aged sea spray were 0.26 ± 0.01 and 0.87 ± 0.02 μg/m 3, respectively. At Lucas heights, fresh and aged sea spray contributed to 11% and 21% of PM2.5, respectively. At Richmond fresh and aged sea spray contributed to 4.8 ± 0.35 and 16 ± 0.5% of the PM2.5, respectively. The Cl/Na ratios of aged sea spray at Lucas Heights and Richmond were 0.72 and 0.87, respectively, in comparison to 1.54 for fresh sea salt. At Richmond the corresponding Ca/Na and K/Na ratios were both 0.037 (close to that of seawater), and at Lucas Heights, the corresponding ratios were 0.038 and 0.026, respectively. Back trajectory and Radon-222 analysis demonstrated that the largest concentrations of aged sea spray occur when the air masses had travelled over regions of anthropogenic sources. This confirms an interaction between anthropogenic precursors and sea spray that liberates chlorine enabling it to contribute to other chemical reactions in the atmosphere, e.g. resulting in an increase in the formation of ozone. Highlights: Cl depletion in PM2.5 of sea salt origin was studied at two sites in Sydney. Radon-222 was used to identify air masses with the least terrestrial influence. At 18.4 km from the coast, fresh and aged sea spray accounted for 32% of all PM2.5. At 58 km from the coast, fresh and aged sea spray accounted for 20.8% of all PM2.5. Anthropogenic sources had high impact on the formation of sea aged PM2.5.